Format Matters Standards, Practices, and Politics in Media Cultures - Jancovic, Marek; Volmar, Axel; Schneider, Alexandra (meson press, 2019)
From TIFF files to TED talks, from book sizes to blues stations-the term "format" circulates in a staggering array of contexts and applies to entirely dissimilar objects and practices. How can such a pliable notion meaningfully function as an instrument of classification in so many industries and scientific communities? Comprising a wide range of case studies on the standards, practices, and politics of formats from scholars of photography, film, radio, television, and the Internet, Format Matters charts the many ways in which formats shape and are shaped by past and present media cultures. This volume represents the first sustained collaborative effort to advance the emerging field of format studies.